A Biphasic Pleural Tumor with Features of an Epithelioid and Small Cell Mesothelioma: Morphologic and Molecular Findings. (15th June 2016) - Hackman, Sarah; Hammer, Richard D.; Layfield, Lester
Abstract : Malignant mesotheliomas are generally classified into epithelioid, sarcomatoid, desmoplastic, and biphasic types with rare reports of a small cell form. These small cell variants display some morphologic overlap with desmoplastic small round cell tumors (DSRCTs) which generally occur within the abdominal cavity of young males and are defined by a characteristic t(11;22)(p13;q12) translocation. However, there are rare reports of DSRCTs lacking this translocation. We present a 78-year-old man with a pleura-based biphasic neoplasm with features of both epithelioid mesothelioma and a small cell blastema-like neoplasm. The epithelioid portion showed IHC reactivity for pan cytokeratin, CK5/6, D2-40, and calretinin and the small cell portion marked with CD99, pan cytokeratin, WT1, FLI1, S100, CD200, MyoD1, and CD15. Fluorescence in situ hybridization testing for the t(11;22)(p13;q12) translocation disclosed loss of the EWSR1 gene in 94% of tumor cell nuclei, but there was no evidence of the classic translocation. Array based-comparative genomic hybridization (a-CGH) confirmed the tumor had numerous chromosome copy number losses, including 11p15.5-p11.12 and 22q12.1-q13.33, with loss of the EWSR1 and WT1 gene regions. Herein, we report novel complex CGH findings in a biphasic tumor and review the molecular genetic alterations in both mesothelioma and DSRCTs.